Corrosion Rate of Stainless Steel 304 in HNO3 Solution - Hendrikus Dwijayanto Wibowo Sutarjo (HM Publisher, 2021)
This literature review was aims to describe corrosion rate stainless steel 304 in sulfuric acid. Immerse process do in 700C temperature for 6 hours and than in 29oC temperature for 18 hours every day. This condition aim to get closer to the actual use in the manufacture of tubes of reactor SAMOP (sub critical assembly for Mo99Prad action). Specimen after TIG welding and electric arc welding cleaned from crust and than measured, drawing, balanced, and record the first weight. The survey findings show heavy shrinkage sample, it is well visible on the corrosion pH 0.5 in electric arc welding of 0.105 gram/dm2/month for corrosion 0.026 gram/dm2/month without welding and pH 0.2, arc welding of 0.045 gram/dm2/month, pH 0.2 no Las 0.02 gram/dm2/month. Specimen that has been welded have significant differences in corrosion rate compare to specimen that have not weld.